Hubungan Gaya Hidup Terhadap Kejadian Menarche Pada Siswi SMP Negeri 02 di Kota Bengkulu Tahun 2025 - Murniati Murniati; Taufianie Rossita; Nuche Marlianto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Menarche is the first menstruation that marks the maturity of the reproductive system in adolescent girls. Changes in adolescent lifestyle, such as a diet high in fat and sugar, low physical activity, and irregular sleep patterns, are thought to affect the timing of menarche. An unhealthy lifestyle can affect the balance of reproductive hormones. This study aims to determine the relationship between lifestyle and the occurrence of menarche among female students at SMP Negeri 02 Kota Bengkulu in 2025. This study uses a correlational analytical design with a cross-sectional approach. The study population consisted of 209 seventh-grade female students, with a sample of 68 respondents selected using proportional stratified random sampling. Data collection used a questionnaire on lifestyle and the occurrence of menarche. Data analysis was performed univariately and bivariately using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents had a healthy lifestyle (38 students, 55.9%) and 38 students (55.9%) had experienced menarche. The Chi-Square test yielded a p-value of 0.019 (p ≤ 0.05), indicating a significant relationship between lifestyle and the occurrence of menarche. It is recommended that schools improve reproductive health education and the implementation of a healthy lifestyle. Adolescent girls are expected to maintain a healthy diet, physical activity, and sleep patterns to support optimal reproductive health.